Perlindungan Hukum Pengguna Mobile Banking Sebagai Korban Kejahatan Melalui Internet Ditinjau Dari Hukum Positif - Eveline Ivanca; Hery Firmansyah (UNES Law Review, 2023)
Information technology can be used to commit a wide variety of crimes, including online gambling, automated teller machine theft, corporate data theft, and fraud through electronic media. As victims of fraud crimes often lack access to legal assistance and receive little attention from the criminal justice system as a whole - especially in terms of human rights - laws are therefore needed to control them. The author concludes that Article 28 paragraph (1) of the Electronic Information and Transaction Law and Article 378 of the Electronic Information and Transaction Law regulate in terms of positive law regarding the legal protection of mobile banking users as victims of internet crimes. Article 378 of the Criminal Code, which provides legal protection to consumers of M-Banking users against potential losses, is evident in the Law on the protection of witnesses and victims, a special regulation relating to the protection of victims. Even so, witness and victim protection laws offer protection to victims from illegal activities that place witnesses and victims in dangerous situations that could endanger their lives. Electronic information and technology laws offer protection to suspects and defendants through case resolution and criminal sanctions; in contrast, the criminal procedure code protects victims through the right to report, the right to organize public prosecutors, and the right to combine criminal and civil prosecutions to obtain compensation.